Understanding Vertical Urban Development in Changing the Spatial Movement of Residents Using Agent-based Modelling Approach - Agung Wahyudi (Journal of Regional and City Planning, 2018)
Abstract. Vertical urban development (VUD) flourishes in various cities that pursue the vision of a compact and sustainable urban development. The implementations of VUD have yielded positive impacts for both the government and the public by reducing the transport cost for residents and increasing accessibility. Despite implementation of VUD offering various advantages in urban planning, the majority of past urban models represent urban growth as an expansive type of development. Hence, the implementation of VUD in urban modelling has not been explored. This study aimed to investigate the influence of VUD on the movement of residents by differentiating building height. Using an agent-based modelling approach on a synthetic case study, the simulation results revealed a reduced level of agents' movement on non-built up land while an increased movement was observed around and within built-up land. The preliminary findings of this research reveal the quantitative impact of VUD on resident movement.Keywords. Agent-based model, transit-oriented development, vertical development.Abstrak. Pembangunan perkotaan vertikal (VUD) berkembang di berbagai kota yang mengejar visi pembangunan perkotaan yang kompak dan berkelanjutan. Implementasi VUD telah menghasilkan dampak positif bagi pemerintah dan masyarakat dengan mengurangi biaya transportasi untuk penduduk dan meningkatkan aksesibilitas. Meskipun penerapan VUD menawarkan berbagai keuntungan dalam perencanaan kota, mayoritas model perkotaan di masa lalu mewakili pertumbuhan perkotaan sebagai jenis pembangunan yang ekspansif. Oleh karena itu, implementasi VUD dalam pemodelan perkotaan belum tereksplorasi. Penelitian ini bertujuan untuk mengetahui pengaruh VUD terhadap pergerakan penduduk dengan membedakan tinggi bangunan. Dengan menggunakan pendekatan pemodelan berbasis agen pada studi kasus sintetis, hasil simulasi menunjukkan penurunan tingkat pergerakan agen di lahan yang tidak terbangun sementara ada pergerakan yang meningkat diamati di sekitar dan di dalam lahan yang terbangun. Temuan awal penelitian ini mengungkapkan dampak kuantitatif VUD pada pergerakan penduduk.Kata kunci. Model berbasis agen, pengembangan berorientasi transit, pengembangan vertikal.